Development and characterization of 15 microsatellite markers for Cephalotaxus fortunei (Cephalotaxaceae)1. (16th May 2016) - Wang, Chunbo; Guo, Zhiyou; Huang, Xilian; Huang, Lu
Abstract : Premise of the study: To survey population variation and the adaptive evolution of Cephalotaxus fortunei (Cephalotaxaceae), an endemic and endangered conifer in China, microsatellite markers were developed and characterized for this species. Methods and Results: Based on the Fast Isolation by AFLP of Sequences COntaining repeats (FIASCO) protocol, 15 microsatellite markers were developed for C. fortunei, 13 of which were polymorphic within a sample of 75 individuals representing five natural populations. The number of alleles per locus ranged from one to seven. The expected and observed heterozygosities were 0.108–0.738 and 0.000–1.000, respectively. Ten polymorphic loci were also successfully amplified in C. oliveri . Conclusions: These polymorphic loci provide a valuable tool for population genetic analysis of C. fortunei, which will contribute to its management and conservation.